Person-Centered Approach to Diabetes Care - Abdul Majid, Hariyati Shahrima binti (International Journal of Human and Health Sciences (IJHHS), 2024)
A major challenge healthcare providers face is to ensure that patients adhere to medication and maintain behavioral changes they make after receiving their diagnosis. Among the factors that contribute to nonadherence to medication and failure to sustain behavior changes are knowledge and perception of disease, lack of motivation to change, diabetes distress and burnout, and lack of social support. This session will highlight the importance of patient-centered communication and recommend some strategies that can be used by healthcare providers in their setting to engage with their patients, improve patients’ success in sustaining the behavioral changes made, thus, managing their diabetes better. This session will focus on ways to (1) foster relationship between healthcare providers, patients and family members (2) gather information, (3) provide information, (4) make collaborative decisions, (5) respond to emotions, and (6) enable disease- and treatment-related behavior. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S20